Research on the evaluation method of surface roughness in CFRP grinding based on mobile computing. (5th September 2019) - Xie, Penghua; Lv, Ming
Mobile computing techniques have facilitated our life greatly with their convenience and practicability. As a new material, Carbon Fibre-Reinforced Plastic (CFRP) has excellent properties. Nevertheless, the anisotropy of CFRP causes difficulty in evaluation of the surface quality after machining. In order to take full advantage of computing image processing technology in a mobile computing environment, this paper proposes a novel method for the surface roughness evaluation based on micro-vision using texture features value extracted by Gabor transform. By analysing the relationship between texture features value and surface roughness three-dimensional evaluation parameter Sq, the paper comes to a conclusion that the surface roughness can be evaluated by the texture features value entropy value (H). The experiments show that the method is superior to the evaluation of surface roughness in CFRP grinding with slight difference, and the convenience of image processing is improved by using mobile equipment and wireless network.